Experimental Measurement of Defects Propagation for a Passenger Car Tire Casing under Dynamic Loading - Vavro, Jan; Vavro, Jan; Klimek, Lukas; Taraba, Milos; Domanski, Tomasz; Saternus, Zbigniew; Dubcova, Petra (Manufacturing Technology Journal, 2025)
The given paper deals with the defects propagation in car tires for passenger vehicles under dynamic loading. The occurrence of defects has the significant influence on the lifetime and quality of the tire, especially during its operation as a part of the vehicle. The given defects are closely connected with a safety in road traffic. The aim of the study was to carry out a non-destructive analysis of the car tire for the purpose to analyze the defects propagation as well as to introduce the defects classification and their location along with the whole course of rupture as a result of increasing speed, loading and the number of hours or kilometers driven. During the analysis, we used a non-destructive method for detecting defects using a non-destructive analyzer that works on the principle of shearography. The experimental measurement was carried out for 12 car tires. The measurement results are displayed from the non-destructive analyzer in the form of protocols from measurement and video display. The evaluation of the results of the measurement for the propagation of defects is displayed graphically. In relation to the tire casing, the analysis of the defects propagation can help design engineers to solve critical issues by choosing the right material, modifying dimensions of individual components or even by redesigning the overall construction of the tire casing and thus to increase the safety from the as-pect of vehicle operation.
Keywords: Measurement; Pressure; Dynamic loading; Non-destructive method; Shearograph